Alvopem® (pemetrexed) safety assessment in patients with non-small cell lung cancer or malignant pleural mesothelioma: a post-marketing surveillance - Sharareh Seifi; Babak Salimi; Zahra Esfahani Monfared; Cyrus Sabahi; Hamidreza Kafi; Adnan Khosravi (Taylor & Francis Group, 2023)
Abstract Background Lung cancer is the leading cause of cancer deaths worldwide in both men and women, and non-small cell lung cancer (NSCLC) accounts for the majority (~ 85%) of lung cancers. This post-marketing surveillance (PMS) study aimed to evaluate the safety of Pemetrexed (Alvopem®, NanoAlvand, Iran) in Iranian patients with lung cancer or mesothelioma. Methods The present study is an observational, single-center, open-label, and post-authorization study. All eligible non-squamous NSCLC and malignant pleural mesothelioma (MPM) patients who received pemetrexed based on the physicians' decision, were enrolled. Results A total of 199 patients with non-squamous NSCLC [186 patients (93.47%) or MPM (12 patients (6.03%)] were enrolled from March 2016 to February 2020. The most common reported adverse event (AE) was anemia (89.39%), followed by neutropenia (28.79%) and leukopenia (24.75%). The most important grade 3 AEs were anemia and neutropenia, with the incidence rate of 3.54% and 7.58%, respectively. No grade 4 AEs were reported. Moreover, the results of our study showed negative statistically significant correlations between patients' age and mean neutrophil count (r = − 0.17; P = 0.0156) and hemoglobin (r = − 0.16; P = 0.0201) in all six visits. Conclusions The results of this open-label, observational PMS showed that Pemetrexed (Alvopem®) is safe in patients with non-squamous NSCLC patients receiving pemetrexed-containing regimens. Trial registration: The trial was registered at ClinicalTrials.gov (NCT04843007) in April 13th, 2021.